2014
DOI: 10.1002/cbic.201300646
|View full text |Cite
|
Sign up to set email alerts
|

Functional Investigations of Thromboxane Synthase (CYP5A1) in Lipid Bilayers of Nanodiscs

Abstract: CYP5A1 is a membrane-associated cytochrome P450 that metabolizes the cyclooxygenase product prostaglandin (PGH2 ) into thromboxane A2 (TXA2 ), a potent inducer of vasoconstriction and platelet aggregation. Although CYP5A1 is an ER-bound protein, the role of membranes in modulating the thermodynamics and kinetics of substrate binding to this protein has not been elucidated. In this work, we incorporated thromboxane synthase into lipid bilayers of nanodiscs for functional studies. We measured the redox potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
0
23
0
2
Order By: Relevance
“…While seminal studies correctly identified the general nature of the protein-membrane binding and topology (5), more recent examples have elucidated the interactions at the molecular and atomistic levels (6-8). Notably, P450 interactions with membranes have been shown to regulate ligand binding mechanisms (9), membrane depth of insertion (10), redox potentials (11), enzyme stability (12), structure and orientation (6). Additionally, advanced computational approaches have revealed the dynamic nature of CYPs and how their hydrophobic motifs interact with the membrane bilayer (6, 8).…”
Section: Introductionmentioning
confidence: 99%
“…While seminal studies correctly identified the general nature of the protein-membrane binding and topology (5), more recent examples have elucidated the interactions at the molecular and atomistic levels (6-8). Notably, P450 interactions with membranes have been shown to regulate ligand binding mechanisms (9), membrane depth of insertion (10), redox potentials (11), enzyme stability (12), structure and orientation (6). Additionally, advanced computational approaches have revealed the dynamic nature of CYPs and how their hydrophobic motifs interact with the membrane bilayer (6, 8).…”
Section: Introductionmentioning
confidence: 99%
“…For all studies with recombinant protein, we used the nanoscale lipid bilayers of nanodiscs (ND) to solubilize and stabilize membrane-bound CYP2J2. These model membranes have been previously used to functionally stabilize membrane protein in solution and on surfaces (Nath et al, 2007;Bayburt and Sligar, 2010;Denisov and Sligar, 2011;Das et al, 2014;Orlando et al, 2014). Importantly, the use of these model membranes significantly reduced scattering and enabled spectroscopic characterization by increasing the solubility of the hydrophobic lipid substrates and membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…5A). We previously showed that TXAS facilitates robust biophysical studies in nanodiscs compared with naked protein in detergent solution (Das et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Thromboxane synthase (TXAS) was expressed and purified as previously mentioned (Das et al, 2014). The gene for TXAS was obtained from OriGene (Rockville, MD) and modified at the N terminus for expression in Escherichia coli as described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation